2017
DOI: 10.1007/s00408-017-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soluble VCAM-1 and Normal P-Selectin in Cystic Fibrosis: a Cross-Sectional Study

Abstract: PurposeAs life expectancy in cystic fibrosis (CF) increases, questions regarding its potential impact on cardiovascular health arise. Soluble vascular cell adhesion molecule 1 (sVCAM-1), P-selectin (sP-selectin) are proposed as biomarkers of cardiovascular disease. We aimed to: compare their concentrations in clinically stable CF patients and healthy subjects (HS) and verify whether they independently correlate with CF characteristics.MethodsSerum sVCAM-1 and sP-selectin levels were measured using ELISA. CF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…Accordingly, the combination treatment of VX-770 + VX-809 (Orkambi®) was able to partially rescue the pro-inflammatory phenotype of CF patient-derived ECs as measured by inflammatory marker gene expression and leukocyte adhesion. Also, our results are in accordance with earlier findings in CF patients where increased soluble EC activation molecules were detected in the plasma and serum, and correlating in some cases, with impaired lung function [55][56][57][58][59][60] .…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the combination treatment of VX-770 + VX-809 (Orkambi®) was able to partially rescue the pro-inflammatory phenotype of CF patient-derived ECs as measured by inflammatory marker gene expression and leukocyte adhesion. Also, our results are in accordance with earlier findings in CF patients where increased soluble EC activation molecules were detected in the plasma and serum, and correlating in some cases, with impaired lung function [55][56][57][58][59][60] .…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, it has been proposed that the activation of VCAM-1 and P-selectin increase platelets function and thrombogenic capacity thereby caution must be taken when developing a target delivery system based on endothelial adhesion molecules [ 203 ]. Meanwhile, comparable levels of VCAM-1 and P-selectin are present in the vascular system of different tissues, some of them likely secreted by ECs following inflammation [ 204 ]. The broad distribution of VCAM-1 and P-selectin on the luminal surface of the vascular network, along with considerable serum levels of these proteins, raises the possibility of non-specific binding and exosome neutralization before BBB cross.…”
Section: Surface Modification Of Exosomes; An Efficient Strategy To Increase Bbb Crossmentioning
confidence: 99%
“…Previous studies have revealed that proposed biomarkers, VCAM-1, ICAM-1, and CD62P with higher concentrations are independently associated with fibrosis [26,27]. To investigate the role of LCG on the vascular fibrosis in DMED rats, the VCAM-1, ICAM-1, and CD62P levels in serum samples of rats were assayed with flow cytometry.…”
Section: Lcg Reduced Vascular Fibrosis Markers Expression In the Seramentioning
confidence: 99%